Structure-function relationships in peripheral nerve contributions to diabetic peripheral neuropathy - Frank, Tessa; Nawroth, Peter Paul; Kuner, Rohini (Pain, 2019)
AbstractDiabetes mellitus (DM) is a major global health concern, affecting more than 9% of the world population. The most common complication of DM is diabetic peripheral neuropathy (DPN), which leads to neuropathic pain in as many as 50% of patients. Despite its prevalence, there is neither good pr
Gesehen am 24.02.2020